Microvascular invasion and early recurrence of hepatocellular carcinoma after CT-guided radiofrequency ablation: risk factor analysis - Liu, Yuyan; Zhao, Xiaoyang; Li, Lupeng; Cao, Huicun (Frontiers in Oncology, 2025)
BackgroundHepatocellular carcinoma (HCC) remains a major global health challenge, and microvascular invasion (MVI) and early recurrence pose significant obstacles to effective treatment. Identifying the risk factors associated with these complications following computed tomography (CT)-guided radiofrequency ablation (RFA) is essential for optimizing patient management and improving treatment outcomes.MethodsA retrospective analysis was conducted from January 2020 to January 2022, involving 186 patients who underwent CT-guided RFA for primary HCC at a single institution. The study assessed tumor characteristics, liver function, and post-treatment outcomes to identify predictors of MVI and early recurrence. Logistic regression and machine learning were employed to determine statistically significant risk factors.ResultsMultiple tumors, incomplete capsules, irregular tumor margins, and rapid portal venous washout were identified as significant predictors of MVI. Similarly, rapid portal venous phase washout, tumor internal necrosis, MVI, multiple tumors, and incomplete capsule integrity were strongly associated with early recurrence. The results of the logistic regression machine learning further enhance the reliability of the current findings.ConclusionPatients with HCC exhibiting certain high-risk features are susceptible to MVI and early recurrence following CT-guided RFA. The identified risk factors suggest the need for enhanced monitoring and personalized therapeutic strategies to improve patient outcomes.